Designing and setting up of a perching vehicle test facility - Tan, Zheng Wen. (2011)
The notion of perching micro aerial vehicles (MAVs) has drawn tremendous interest in the research community. Tremendous potential lies in a perching MAV as a platform for long endurance surveillance by maintaining a low powered perch state.